The Effect of Carbon Emission Disclosure and Tax Avoidance on Firm Value with Dividends as A Moderating Factor - Santo, Vianty Adella (Indonesian Management and Accounting Research, 2024)
This study examines the effect of disclosure of carbon emissions and tax avoidance on firm value with dividends as a moderator. The population in this research are those companies listed on the Indonesia Stock Exchange from 2015 to 2020. The data obtained are secondary data using a purposive sampling method with 144 observations. This research used multiple regression analysis. The results showed that the company's carbon emission disclosure positively impacts the firm's value, and tax avoidance does not negatively impact the firm's value. In addition, this research found that dividends neither strengthen the positive impact of carbon emission disclosure nor weaken the negative impact of tax avoidance on the firm's value.